The Effect of Financial Rewards on Employee Work Motivation: An Experimental Study at SPD Speedometer Automotive Company - Sekar Ayu Fajar Pertiwi; Siti Khofifatul Mardhiyyah; Ikhsan Badruz Zaman; Noviani Putri Pratama; Siti Rahmaliya (Green Publisher Indonesia, 2025)
In today's highly competitive business landscape, companies must swiftly adapt to changes and ensure that their employees remain motivated to achieve optimal productivity levels. One crucial factor in enhancing work motivation is the implementation of an effective reward system. This study aims to examine the effect of financial rewards on employee work motivation at SPD Speedometer, an automotive company. Employing a quasi-experimental design with a post-test-only control group, the research involved 60 employees divided into two groups: an experimental group receiving financial rewards and a control group receiving none. Work motivation was measured using a scale adapted from George and Jones (2012), covering three indicators: direction of behavior, level of effort, and level of persistence. The data were analyzed using the Mann-Whitney test, which revealed a significant difference in work motivation between the two groups, indicating that financial rewards substantially enhance employee motivation. These findings align with reinforcement theory and Herzberg's two-factor theory, both of which identify financial incentives as pivotal extrinsic motivators that drive positive work behavior. The practical implication suggests that a well-structured and equitable financial reward system can serve as an effective managerial strategy to boost employee motivation and productivity, particularly in the automotive industry.